THE DRIVING FACTORS FOR USING QR CODES AND DIGITAL WALLETS IN BLITAR - Meirezaldi, Onni; Hisyam Tualeka, Safarudin (LPSDI Bina Patria, 2024)
This study examines the significance of perceived ease of use and usefulness in driving the intention to use cashless transactions through QR codes and digital wallets in Blitar, a small city in East Java Province, with most informal workers lacking access to traditional banking services. Thru 220 respondents completing 22 research questionnaires, the findings indicate that perceived ease of use and usefulness positively and significantly affect the intention to use cashless transactions. However, the direct effect of perceived ease of use did not show statistical significance. These insights offer valuable guidance for stakeholders aiming to create a user-friendly technological landscape. Emphasizing the importance of perceived usefulness in motivating cashless transaction adoption, especially in communities with limited banking access, stakeholders can design strategies to enhance usability and effectively communicate the benefits. Further examination is necessary to fully understand the influence of perceived ease of use in this context. These findings contribute to ongoing digital transformation and financial inclusion efforts, particularly in underserved communities like Blitar.